Challenging Fathers. Issue 3 (1st September 2016) - Kuchuck, Steven
Abstract : In this paper, I explore what I perceive to be the curative elements of Freud's one-session consultation with Margarethe Lutz. There are numerous lessons to be learned about Freud's use of his subjectivity, direct suggestion, transference–countertransference, and other points of interest for contemporary clinicians. In this meeting we witness a departure from—or a new understanding of—classical technique and in its place find a style that we might be more apt to think of as relational. Elements of my own subjective responses to Lutz's recollection and the writing of this response are also discussed.